Dripping, Jetting and Regime Transition of Droplet Formation in a Buoyancy-Assisted Microfluidic Device - Chaoqun Shen; Feifan Liu; Liangyu Wu; Cheng Yu; Wei Yu (Micromachines, 2020)
Buoyancy-assisted droplet formation in a quiescent continuous phase is an effective technique to produce highly monodispersed droplets, especially millimetric droplets. A comprehensive study combining visualization experiment and numerical simulation was carried out to explore the underlying physics of single droplet generation in a buoyancy-assisted microfluidic device. Typical regimes, including dripping and jetting, were examined to gain a deep insight into the hydrodynamic difference between the regimes. Particularly, the transition from dripping regime to jetting regime was investigated to give an in-depth understanding of the transitional behaviors. The effects of interfacial tension coefficient on the droplet size and formation regimes are discussed, and a regime diagram is summarized. The results show that oscillation of the interface in dripping regimes after detachment is caused by the locally accelerated fluid during the neck pinching process. Droplet formation patterns with the characteristics of both dripping regime and jetting regime are observed and recognized as the transitional regime, and the interface oscillation lasts longer than that in dripping regime, implying intensive competition between interfacial tension and inertial force. Reducing interfacial tension coefficient results in the dripping-to-jetting transition occurring at a lower flow rate of the dispersed phase. The regime diagram indicates that only the inertial force is the indispensable condition of triggering the transition from dripping to jetting.